Temporal Analysis in Outcomes of Long-Term Mechanical Circulatory Support: Retrospective Study - Ondrusek, Matej; Artemiou, Panagiotis; Bezak, Branislav; Gasparovic, Ivo; By, Theo MMH de; Durdik, Stefan; Lesny, Peter; Goncalvesova, Eva; Hulman, Michal (The Thoracic and Cardiovascular Surgeon, 2024)
Background Mechanical assist device indications have changed in recent years. Reduced incidence of complications, better survival, and the third generation of mechanical support devices contributed to this change. In this single-center study, we focused on two time periods that are characterized by the use of different types of mechanical support devices, different patient characteristics, and change in the indications.Methods The data were processed from the European Registry for Patients with Mechanical Circulatory Support (EUROMACS). We retrospectively defined two time intervals to reflect changes in ventricular assist device technology (period 1: 2007–2015; period 2: 2016–20222). A total of 181 patients underwent left ventricular assist device implantation. Device utilization was the following: HeartMate II = 52 (76.4%) and HeartWare = 16 (23.6%) in period 1 and HeartMate II = 2 (1.8%), HeartMate 3 = 70 (61:9%), HeartWare = 29 (25.7%), SynCardia TAH = 10 (8.8%), and BerlinHeart EXCOR = 2 (1.8%) in period 2. The outcomes of the time intervals were analyzed and evaluated.Results Survival was significantly higher during the second time period. Multivariate analysis revealed that age and bypass pump time are independent predictors of mortality. Idiopathic cardiomyopathy, bypass time, and the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) score are independent predictors of adverse events. Furthermore, the first period was noted to be at an increased risk of the following adverse events: pump thrombosis, gastrointestinal bleeding, and bleeding events.Conclusion Despite the higher risk profile of the patients and persistent challenges, during the second period, there was a significant decrease in mortality and morbidity. The use of the HeartMate 3 device may have contributed to this result.
Keywords: left ventricular assist device; outcomes; temporal analysis